A survey of talent identification and development processes in the youth academies of professional soccer clubs from around the world - Ford, P. R.; Delgado Bordonau, J. L.; Bonanno, D.; Tavares, J.; Groenendijk, C.; Fink, C.; Gualtieri, D.; Gregson, W.; Varley, M. C.; Weston, M.; Lolli, L.; Platt , D.; et al. (Journal of Sports Sciences, 2020)
Talent identification (TID) and development (TDE) are large fields in professional soccer and in science. However, TID and TDE processes in youth academies have not been assessed in detail. As such, our aim was to survey professional clubs from around the world about their youth academy TID and TDE processes, with 29 clubs responding to the survey. TID and TDE processes changed as a function of player age. TID processes involved finding the best players locally and regionally, but for older players the search widened to nationally and internationally for the needs of the first team. Clubs used a multidisciplinary approach to TID, but more so with older players. Median number of academy players was 80, 100, and 66 players at 8-11 years, 12-16 years, and 17-21 years, respectively. Annual player turnover in the most recent season (selections/de-selections) was 29% across all age groups, with competition from other clubs cited as a limitation to TID. TDE processes involved weekly matches and 3-5 training sessions per week led by experienced, well-qualified coaches, with most clubs providing players with academic education, residency and transportation services. Our findings extend previous research assessing professional soccer youth academy TID and TDE processes by quantifying worldwide practices.